On Bootstrap Algorithms in Survey Sampling - Tomasz Żądło (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The aim of this paper is to present bootstrap algorithms for measuring the accuracy of estimation and prediction in design-based and model-based approaches in survey sampling and small area estimation. Three proposals of prediction-mean squared error estimators are also examined.